Metaplastic breast cancer: Prognostic and therapeutic considerations. Issue 1 (12th October 2020) - Corso, Giovanni; Frassoni, Samuele; Girardi, Antonia; De Camilli, Elisa; Montagna, Emilia; Intra, Mattia; Bottiglieri, Luca; Margherita De Scalzi, Alessandra; Fanianos, Denise Mattar; Magnoni, Francesca; Invento, Alessandra; Toesca, Antonio; et al.
Abstract: Introduction: Metaplastic breast cancer (MBC) is a rare condition of breast tumor with different subtypes, considered a disease with worse prognosis; treatments and survival are often unclear and conflicting. Methods: We consecutively collected 153 primary MBCs of different subtypes. Breast surgery, neoadjuvant or adjuvant treatment, clinic‐pathological factors, number and type of events during follow‐up were considered to evaluate overall survival (OS) and invasive disease‐free survival (IDFS). Results: The majority of MBC was triple‐negative (TN) subtype (88.7%), G3 (95.3%), pN0 (70.6%), and with high levels of Ki‐67 (93.5%). For OS and IDFS, no significant associations were seen between the different MBC subtypes. The matched triple‐negative MBC (TNMBC) and ductal TNBC cohorts had similar prognosis both in terms of OS ( p  = .411) and IDFS ( p  = .981). We observed a positive trend for TNMBC patients treated in the adjuvant setting with the cyclofosfamide, methotrexate, 5‐fluorouracil protocol for better OS ( p  = .090) and IDFS ( p  = .087). A poor or absent response rate was observed in the neoadjuvant setting. Conclusion: Our results demonstrate that metaplastic and ductal breast cancers with TN phenotype are similar in terms of overall and disease‐free survival. Metaplastic cancers are poorly responsive to neoadjuvant treatment, and in the absence of novel targeted therapies, surgical treatment remains the first choice.